PENYELESAIAN PERKARA PERDATA MELALUI GUGATAN SEDERHANA (SMALL CLAIM COURT) PADA STUDI KASUS PUTUSAN NO. 11/PDT.G.S/2023/PN.JKT.PST - Moina, Moina; Sahputra, Rilawadi; Sitompul, Ariman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to analyze the application of law in the settlement of small claims in cases of default based on a case study No. 11/Pdt.G.S/2023/PN.Jkt.Pst between PT Digital Commerce Indonesia as the Plaintiff and PT Ezone Asia Indonesia as the Defendant. The dispute arose due to the Defendant's negligence in paying the remaining payment of Rp 317,659,365 for electronic goods and office equipment that had been received according to the 2019 sales and purchase agreement. This research uses a descriptive-analytical method with a normative juridical approach, and relies on literature studies as the main data source. The main focus is on the technical implementation of procedures, changes in the claim value limit, and legal innovations such as the use of the e-court system and the introduction of verstek and verzet mechanisms. The results of the study indicate that the application of PERMA No. 4 of 2019 in this case provides greater flexibility in the process of resolving small-value civil cases. The Central Jakarta District Court succeeded in resolving the case efficiently, quickly, and simply without sacrificing substantial justice. This is evident in the clarity of the decisions, the short resolution time, and its compliance with applicable legal norms. Thus, the small claims system, as stipulated in Supreme Court Regulation No. 4 of 2019, has proven effective in increasing public access to justice and providing responsive legal solutions to the dynamics of small-value civil disputes.Keyword: Simple Lawsuit, Breach of Contract, PERMA No. 4 of 2019, Sale and Purchase Agreement, Effectiveness of the Judiciary.Abstrak: Penelitian ini bertujuan untuk menganalisis penerapan hukum dalam penyelesaian gugatan sederhana terhadap kasus wanprestasi berdasarkan studi kasus perkara No. 11/Pdt.G.S/2023/PN.Jkt.Pst antara PT Digital Commerce Indonesia sebagai Penggugat dan PT Ezone Asia Indonesia sebagai Tergugat. Sengketa timbul akibat kelalaian Tergugat dalam melunasi sisa pembayaran sebesar Rp 317.659.365 atas barang elektronik dan peralatan kantor yang telah diterima sesuai perjanjian jual beli tahun 2019. Penelitian ini menggunakan metode deskriptif-analitis dengan pendekatan yuridis normatif, serta mengandalkan studi kepustakaan sebagai sumber data utama. Fokus utama tertuju pada implementasi teknis prosedur, perubahan batas nilai gugatan, serta inovasi hukum seperti penggunaan sistem e-court dan pengenalan mekanisme verstek dan verzet. Hasil penelitian menunjukkan bahwa penerapan PERMA No. 4 Tahun 2019 dalam perkara ini memberikan fleksibilitas yang lebih besar dalam proses penyelesaian perkara perdata bernilai kecil. Pengadilan Negeri Jakarta Pusat berhasil menyelesaikan perkara secara efisien, cepat, dan sederhana tanpa mengorbankan keadilan substansial. Hal ini terlihat dari kejelasan putusan, waktu penyelesaian yang singkat, serta kesesuaian dengan norma hukum yang berlaku. Dengan demikian, sistem gugatan sederhana sebagaimana diatur dalam PERMA No. 4 Tahun 2019 terbukti efektif dalam meningkatkan akses terhadap keadilan bagi masyarakat, serta memberikan solusi hukum yang responsif terhadap dinamika sengketa perdata bernilai kecil.Kata kunci: Gugatan Sederhana, Wanprestasi, PERMA No. 4 Tahun 2019, Perjanjian Jual Beli, Efektivitas Peradilan